Upaya Peningkatan Kemampuan Analisis Data Penelitian Menggunakan Software Statistik Bagi Guru-Guru Matematika SMA Kabupaten Pesisir Selatan - Syafriandi, Syafriandi; Amalita, Nonong; Kurniawati, Yenni (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Scientific publication is one of teacherâs duty to increase their rank, form III/b to III/c. Base on interview with Senior High School teachers at Pesisir Selatan regency, we know that difficult for them to produce scientific publication caused by their ability on choosing data analysis technique which relevant to their case, teachers cannot use the statistical software because its not familiar for them, and they have low quality in interpreting data analysis result. To solve the problems, we offer a workshop of data analysis on scientific writing using statistical software. The target audiences of this workshop is a Group of Teachers on Mathematics Major (MGMP) in Pesisir Selatan. In this workshop, participants are given the basic concept and how to write a scientific writing, basic concept of statistics, and introduction to statistical software i.e. Minitab and SPSS. Beside that, with practical work, the participants learn how to use statistical software and interpretate the data analysis result. Result of the workshops are (1) increasing the ability of participants skills on analysis the data using statistical software and interpretate it.